234k views
3 votes
Use completeling the square to solve for x in the equation (x-12)(x+4)=9

User Joe Bobby
by
6.7k points

1 Answer

3 votes

Answer:

x=
4\pm √(73)

Explanation:

First step. Solve the binomial product from the left side of the equation:


(x-12)(x+4)=9


x^2+4x-12x-48=9

Second step. Simplify and move independent terms to the right side of the equation:


x^2-8x=57

Third step. Find a number that multiplied by two gives -8, then square this number and sum it on both sides of the equation:


x^2-8x+16=57+16

Fourth step. Write the left side of the equation as a squared binomial:


(x-4)^2=73

Fifth step. First, take the square root and then add 4 to both sides of the equation to solve for x:


(x-4)=\pm √(73)


x= 4\pm √(73)

User TheoPlatica
by
6.7k points